Time-of-Flight Magnetic Resonance Angiography With Sparse Undersampling and Iterative Reconstruction: Comparison With Conventional Parallel Imaging for Accelerated Imaging. Issue 6 (June 2016) - Yamamoto, Takayuki; Fujimoto, Koji; Okada, Tomohisa; Fushimi, Yasutaka; Stalder, Aurelien F.; Natsuaki, Yutaka; Schmidt, Michaela; Togashi, Kaori
Abstract : Objectives: The aim of this study was to evaluate the clinical feasibility of accelerated time-of-flight (TOF) magnetic resonance angiography with sparse undersampling and iterative reconstruction (sparse TOF). Materials and Methods: The local institutional review board approved the study protocols. Twenty healthy volunteers were recruited (mean age, 31.2 years; age range, 22-52 years; 14 men, 6 women). Both sparse TOF and parallel imaging (PI) TOF were obtained on a 3 T scanner. Acceleration factors were 3, 4, 5, 6, and 8 for sparse TOF (Sp 3×, Sp 4×, Sp 5×, Sp 6×, and Sp 8×, respectively) and 2, 3, 4, and 6 for PI TOF (PI 2×, PI 3×, PI 4×, and PI 6×, respectively). Images were reconstructed on the scanner, and maximum intensity projection images were subjected to visual evaluation, wherein each segment of the major brain arteries was independently evaluated by 2 radiologists on a 4-point scale (1, poor; 2, limited; 3, moderate/good quality for diagnosis; and 4, excellent). As a quantitative evaluation, the apparent contrast-to-background deviation (apparent CBD) was calculated at the level of the basilar artery and the pons. Results: A total number of 1800 segments were subjectively evaluated. There was substantial agreement regarding vessel visualization (κ = 0.759). Sparse TOF received scores above 3 (good for diagnosis) at any acceleration factor up to the third segments of major arteries. The middle and distal segments of PI 4× and PI 6× were graded below 3 (limited or poor diagnostic value). Sp 3×, 4×, 5×, and 6× retained diagnostic information (graded above 3), even at distal segments. The apparent CBD of sparse TOF at any acceleration factor was equivalent to that of PI 2×, whereas the apparent CBD of PI 3×, PI 4×, and PI 6× attenuated with the acceleration factor. Conclusions: Sparse TOF can achieve better image quality relative to PI TOF at higher acceleration factors. The diagnostic quality of distal branches (A2/3, M4, P4) was maintained with Sp 6×, which achieved a shorter acquisition time less than half of PI 2×.